Platycodigenin as Potential Drug Candidate for Alzheimer’s Disease via Modulating Microglial Polarization and Neurite Regeneration - Yang, Zhiyou (Molecules, 2019)
Neuroinflammatory microenvironment, regulating neurite regrowth and neuronal survival, plays a critical role in Alzheimer’s disease (AD). During neuroinflammation, microglia are activated, inducing the release of inflammatory or anti-inflammatory factors depending on their polarization into classical M1 microglia or alternative M2 phenotype. Therefore, optimizing brain microenvironment by small molecule-targeted microglia polarization and promoting neurite regeneration might be a potential therapeutic strategy for AD. In this study, we found platycodigenin, a naturally occurring triterpenoid, promoted M2 polarization and inhibited M1 polarization in lipopolysaccharide (LPS)-stimulated BV2 and primary microglia. Platycodigenin downregulated pro-inflammatory molecules such as interleukin (IL)-1β, tumor necrosis factor (TNF)-α, IL-6 and nitric oxide (NO), while upregulated anti-inflammatory cytokine IL-10. Further investigation confirmed that platycodigenin inhibited cyclooxygenase-2 (Cox2) positive M1 but increased Ym1/2 positive M2 microglial polarization in primary microglia. In addition, platycodigenin significantly decreased LPS-induced the hyperphosphorylation of mitogen-activated protein kinase (MAPK) p38 and nuclear factor-κB (NF-κB) p65 subunits. Furthermore, the inactivation of peroxisome proliferators-activated receptor γ (PPARγ) induced by LPS was completely ameliorated by platycodigenin. Platycodigenin also promoted neurite regeneration and neuronal survival after Aβ treatment in primary cortical neurons. Taken together, our study for the first time clarified that platycodigenin effectively ameliorated LPS-induced inflammation and Aβ-induced neurite atrophy and neuronal death.